Characteristics of Childhood Glaucoma in Kariadi Hospital Semarang - Novi Endah Sulistiyawati; Liana Ekowati (Majalah Oftalmologi Indonesia, 2016)
Background: Glaucoma in childhood is a rare and serious cause of blindness around the world, but itis treatable. Glaucoma is the second leading cause of vision loss in people of all ages around theworld. Childhood glaucoma is estimated to cause a significant percentage of blindness in children,from 1.2% of children in Great Britain, 3% in northern India, to 7% in southern India. The aim of thisstudy is to report the characteristics of childhood glaucoma in Kariadi Hospital Semarang fromJanuary 2012 to December 2014.Methods: We retrospectively evaluated 62 eyes in 37 patients with childhood glaucoma from January2012 to December 2014. Medical records of childhood glaucoma were reviewed to determine thecharacteristics, including the demographic data.Results: Twenty five children (67.6%) with childhood glaucoma are male. The mean age was 4.9years old (range 16 days old to 16 years old). The incidence of bilateral childhood glaucoma was morecommon than unilateral glaucoma which consisted of 25 patients (67.6%) had bilateral glaucoma and12 patients (32.4%) had unilateral glaucoma. Out of 37 patients, 15 patients had congenital glaucoma(40.54%), 13 patients had glaucoma due to secondary glaucoma (35.14%) and 9 patients had juvenileglaucoma (24.32%). Also, the study showed that there were 13 eyes (20.9%) that had CDR ≤0.3, 41eyes (66.2%) had CDR >0.3, 8 eyes (12.9%) with CDR >0.9 and corneal diameter in 13 eyes (20.9%)were <12 mm, 32 eyes (51.6%) were ≥12 mm, and 17 eyes (27.5%) had >13 mm. For the visual acuityafter glaucoma surgery, 7 eyes (11.2%) had blink reflex, 12 eyes (19.3%) had fix and follow, 27 eyes(43.5%) had optotype, 8 eyes (12.9%) had counting fingers, 7 eyes (11.2%) had hand movement, and1 eye (1.6%) had light perception. The accompanying disease of childhood glaucoma were oculartrauma (50%), uveitis (20%), proptosis (20%), and Sturge Weber syndrome (10%).Conclusion: The most frequent childhood glaucoma in Kariadi Hospital Semarang, the first diagnosisat the period of January 2012 to December 2014, were male, bilateral, congenital glaucoma, CDR>0.3, corneal diameter ≥12 mm, averagely occurred at age of 0-4 years, and could occur as result ofadvanced stage of glaucoma. Keywords: childhood glaucoma, congenital glaucoma, characteristics